Best practices in sustainable development goals - Edited by Sujit Kumar Paul; Gireesan, K. (New Delhi Concept Publishing Company, 2025)
Best Practices in Sustainable Development Goals is a book that showcases the models, approaches, and experiences from different parts of the world. This edited book captures some of the best practices in SDGs from the global, the regional, the national and the local, with inputs from number of institutions, organizations and individuals who are working with and (3z(Bworking for sustainable development(3y(B. It reiterates that the journey towards achieving the SDGs is a collective endeavour that requires adaptability, unwavering commitment and resilience from all the stakeholders. As we engage with the SDGs in our own communities and spheres of influence, we shall remain steadfast in our belief and conviction that together, we can create a sustainable, equitable, and prosperous future for all, that includes the flora and fauna as well. It is a wakeup call for each one of us to adopt, follow and sustain the (3z(Becosystem-based approach(3y (Bin our life as a cardinal principle. The time for action is now, and the possibilities are limitless.s
Keywords: Sustainable Development